Higher education reform in Australia: a reflexive modernisation perspective - Pick, David (HERDSA, 2006)
The aim of this paper is to critically examine the Nelson reform agenda for Australian higher education through the theoretical lens of the reflexive modernization thesis. After a brief overview of the main ideas and concepts of reflexive modernization, the principal characteristics of the Australian government's higher education reform agenda are identified and discussed. This paper demonstrates that the Nelson reforms are an intensification of a process begun in the 1980s that is opening the higher education sector to increased competition, privatization, and marketization. Higher education policy has forced universities to undertake rapid and profound change over the past two decades that is radically redefining the nature and purpose of higher education. The trends identified have significant implications in that the Australian higher education sector is being fundamentally transformed through individualization, risk,and reflexivity manifest, for example, in the introduction of a tiered system of universities, a reform of government support for students, and a radical re-arrangement of employment conditions within the sector. These reforms are calling into question the nature and role of universities within Australian society.